Choroidal thickness in children with hyperopic anisometropic amblyopia. Issue 2 (1st November 2013) - Nishi, Tomo; Ueda, Tetsuo; Hasegawa, Taiji; Miyata, Kimie; Ogata, Nahoko
Abstract : Purpose: To determine the choroidal thickness (CT) in the macular area of eyes of children with hyperopic anisometropic amblyopia and to compare the thickness with that of fellow eyes and age-matched controls. Materials and methods: Twenty-five patients (6.6±2.2 years, mean±SD) with hyperopic anisometropic amblyopia and twenty age-matched controls (6.7±1.9 years) were studied. The CT was measured with the enhanced depth imaging programme of a spectral domain optical coherence tomographic instrument in all patients and controls. The CT of the subfoveal area and at 1 mm and 3 mm diameter around the fovea was determined. In addition, the correlation between the CT and axial length was calculated. Results: The mean subfoveal CT was 351.3±54.7 µm in the amblyopic eyes, 283.5±55.2 µm in the fellow eyes and 282.7±73.3 µm in the control eyes. The subfoveal choroid in amblyopic eyes was significantly thicker than that of the fellow eyes and control eyes (p=0.001). There was a significant negative correlation between the subfoveal CT and the axial length in the amblyopic eyes (amblyopic eyes: r =−0.51, p=0.01) and the control eyes ( r =−0.46, p=0.01). Conclusions: The subfoveal choroid of eyes with hyperopic anisometropic amblyopia is significantly thicker than that of the fellow eye and the age-matched controls. The profile of the CT in the amblyopic eyes was different from that of the fellow eyes and control eyes.